Cost benefit analysis of recreational public park (A Case of Tikapur Banglaw Park) - Subedi, Khem Raj (Journal of Tikapur Multiple Campus, 2017)
This paper is based on the Cost Benefit Analysis study of Tikapur Banglaw Park (TBP) of Tikapur Municipality in Kailali district. The main objective of this study is to estimate the recreational benefits of TBP, calculation of consumers' surplus per visitor per trip of individual visitors and calculation of benefit cost ratio of the Park. The Individual Travel Cost Method (ITCM) has been employed to capture the non-market benefits of the Park. This study is based on the survey of 101 visitors of the Park during mid March to mid April 2016. The Poisson regression model has been used to estimate consumer surplus of the visitors. The study shows that visit rate of visitors of Park is inversely correlated with travel cost and age of the visitors and positively correlated with household income of the visitors. The mean consumer's surplus per visitor per trip is estimated to be about NPR 2475. The aggregated consumer surplus for the annual park visitors calculated to be NPR 351 million. The estimated opportunity cost of the Park in terms of agricultural production is about NPR 9.99 million per annum. The total benefit is NPR 355 million and total cost is NPR 130 million. The benefit cost ratio is 27.43. The study clearly finds that the Tikapur Banglaw Park generates significantly higher level of public welfare. Therefore, Tikapur Municipality should formulate timely project intervention to upgrade quality of TBP.